ONLINE LIBRARY SYSTEM (E-Biblio) IN THE FACULTY OF ENGINEERING INDUSTRY - Lorena L., Paul (2003)
This article deals with the development of an Electronic Library System (E-Library), with information and reception services, as well as bibliographic material borrowing, by using a bar code, thus getting rid of unnecessary paperwork. The E-Library System has been proposed by the Software Research and Development Circle CIDESOFT. A system implementation and setting forth is also included.